Peripheral Transcription of NRG-ErbB Pathway Genes Are Upregulated in Treatment-Resistant Schizophrenia - Mostaid, Md Shaki; Lee, Ting Ting; Chana, Gursharan; Sundram, Suresh; Shannon Weickert, Cynthia; Pantelis, Christos; Everall, Ian; Bousman, Chad (Frontiers in Psychiatry, 2017)
Investigation of peripheral gene expression patterns of transcripts within the NRG-ErbB signaling pathway, other than neuregulin-1 (NRG1), among patients with schizophrenia and more specifically treatment-resistant schizophrenia (TRS) is limited. The present study built on our previous work demonstrating elevated levels of NRG1 EGFα, EGFβ and type I(Ig2) containing transcripts in TRS by investigating 11 NRG-ErbB signaling pathway mRNA transcripts (NRG2, ErbB1, ErbB2, ErbB3, ErbB4, PIK3CD, PIK3R3, AKT1, mTOR, P70S6K, eIF4EBP1) in whole blood of TRS patients (N=71) and healthy controls (N=57). We also examined the effect of clozapine exposure on transcript levels using cultured peripheral blood mononuclear cells (PBMCs) from 15 healthy individuals. Five transcripts (ErbB3, PIK3CD, AKT1, P70S6K, eIF4EBP1) were significantly elevated in TRS patients compared to healthy controls but only expression of P70S6K (Pcorrected=0.018), a protein kinase linked to protein synthesis, cell growth, and cell proliferation, survived correction for multiple testing using Benjamini-Hochberg method. Investigation of clinical factors revealed that ErbB2, PIK3CD, PIK3R3, AKT1, mTOR, and P70S6K expression was negatively correlated with duration of illness. However, no transcript was associated with chlorpromazine equivalent dose or clozapine plasma levels, the latter supported by in-vitro PBMC clozapine exposure experiment. Taken together with previously published NRG1 results, our findings suggest an overall upregulation of transcripts within the NRG-ErbB signaling pathway among individuals with schizophrenia some of which attenuate over duration of illness. Follow-up studies are needed to determine if the observed peripheral upregulation of transcripts within the NRG-ErbB signaling pathway are specific to TRS or are a general blood-based marker of schizophrenia.